Association of Medicare Part D Medication Out‐of‐Pocket Costs with Utilization of Statin Medications. (26th December 2012) - Karaca‐Mandic, Pinar; Swenson, Tami; Abraham, Jean M.; Kane, Robert L.
<x xml:space="preserve">Abstract</x> Objectives To examine the association between statin out‐of‐pocket (OOP) costs and utilization among the Medicare Part D population. Data Sources/Study Setting 2006–2008 administrative claims and enrollment data for the 5 percent Medicare sample. Study Design Sample included 346, 583 beneficiary‐year observations of statin users enrolled in stand‐alone prescription drug plans, excluding low‐income subsidy recipients. We estimated the association between a plan's OOP statin costs and statin utilization using an instrumental variable approach to account for potential bias due to plan selection. Adherence was defined as percentage of days covered (PDC) of at least 80 percent. Plan OOP costs were constructed for a representative market basket of statin medications. Analyses controlled for demographic characteristics, cardiovascular disease risk, co‐morbidity presence, and regional characteristics. Principal Findings About 67 percent of the sample had a PDC of at least 80 percent. An increase in annual statin OOP from $200 (50th percentile) to $240 (75th percentile) was associated with a reduction in the rate of adherent beneficiaries from 67 percent to 56 percent (p < .001). Conclusions Greater OOP costs for statins are associated with reductions in statin utilization.